2016
DOI: 10.2147/ijn.s100744
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic inhibition of colon cancer cell growth with nanoemulsion-loaded paclitaxel and PI3K/mTOR dual inhibitor BEZ235 through apoptosis

Abstract: Colon cancer is the third most common cancer in the world, with drug resistance and metastasis being the major challenges to effective treatments. To overcome this, combination therapy with different chemotherapeutics is a common practice. In this study, we demonstrated that paclitaxel (PTX) together with BEZ235 exhibited a synergetic inhibition effect on colon cancer cell growth. Furthermore, nanoemulsion (NE)-loaded PTX and BEZ235 were more effective than the free drug, and a combination treatment of both NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…Therefore, this research has optimized and confirmed the LDH NP system for efficient in vitro delivery of genes to cancer cells, which is believed to be also applicable for the in vivo delivery for cancer gene therapy. 43 , 44 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this research has optimized and confirmed the LDH NP system for efficient in vitro delivery of genes to cancer cells, which is believed to be also applicable for the in vivo delivery for cancer gene therapy. 43 , 44 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we chose the dual PI3K/mTOR inhibitor NVP-BEZ235 to address increased Akt activation in HCC38CisR. Synergy of NVP-BEZ235 has already been demonstrated for paclitaxel in colon cancer cells [ 30 ] and carboplatin in a triple negative breast cancer cell line [ 31 ]. Additionally, NVP-BEZ235 has already proven its ability to enhance cisplatin sensitivity in cisplatin resistant bladder cancer cell lines [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…With PD-L1 regulatory mechanism being elucidated, the development of small molecule inhibitors sheds light on precise knockdown of aberrant oncogene expression. Compared to traditional chemotherapy, chemical inhibitors are more effective and less harmful to normal cells, with much clearer patient subset (4, 106). Like gene silencing method, the usage of chemical inhibitors can ā€œturn offā€ the PD-L1 expression ā€œpipeline.ā€ Thus, the influence of chemical inhibitors on different PD-L1 formats is similar to that of gene silencing, with a potentially slower response depending on the target relevance to PD-L1 expression.…”
Section: Inhibition Of Pd-l1 Regulatory Pathwaysmentioning
confidence: 99%